Efforts to Improve Learning Concentration and Learning Outcomes Through Extracurricular Activities of Wushu Sanda Sports for Junior High School Students - Lilis Maesaroh; Muhamad Suma Wijaya; Julinur Hafid; Rifki Rosad; Anisa Shopiani; Adi Maulana Mahmud (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to examine the differences in learning concentration levels between students who participate in wushu sanda extracurricular sports and those who do not. The research method used is ex post facto with a causal design. The study was conducted at Sasana Bandung Fighter Academy (BFA) with a population of middle school students actively participating in BFA activities. The sampling technique used was total sampling, with 10 students as the research sample. The instrument for measuring concentration was the Grid Concentration Exercise. The results showed a significant difference in learning concentration levels between students who participated in extracurricular sports and those who did not, with a significance value of 0.000 (<0.05). However, there was no significant difference in students’ academic achievement, with a significance value of 0.137 (>0.05). Overall, multivariate analysis indicated that students participating in extracurricular sports had better concentration levels than those who did not. Therefore, extracurricular sports play an important role in improving students’ learning concentration.